(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
This review explores the link between endoplasmic reticulum (ER) stress and leptin resistance in obesity, with a focus on women. ER dysfunction activates stress markers such as XBP1, CHOP, and GRP78, disrupting leptin signaling and promoting metabolic imbalance. Chronic overnutrition induces sustained ER stress, impairing hypothalamic and peripheral leptin pathways. Elevated expression of these markers correlates with obesity severity and metabolic dysfunction, particularly in females due to hormonal and fat distribution differences. Understanding these molecular mechanisms may guide the development of targeted therapies for obesity-related disorders.